REVIEW LITERATURE: INDONESIAN PORT MANAGEMENT STRATEGY WITH TRANSDISCIPLINARY APPROACH COMPARED TO OTHER COUNTRIES IN THE WORLD - Septa Riadi; Eva Anggraini; Yudi Wahyudin (COJ (Coastal and Ocean Journal), 2018)
Research with a transdisciplinary approach aims to encourage integration beyond the boundaries of disciplines, and provide new perspectives in dealing with complex problems. These problems target various aspects, including problems in port management. In Vietnam the main problem of the port is in terms of ecology. While in Hong Kong as one of the largest ports in the world, it also faces problems in regulating the flow of ships and also in ports. Greece and China highlight an equally important study, namely the risk at the port. The port of Turkey has a different approach in attracting ships to dock at its ports, namely non-price aspects such as customer service, service customization and bundling, service expansion, service diversification and additional services and most importantly is the improvement of the company's image through the UK and Australia's CSR having the same problem regarding port privatization. To solve this problem is certainly expected to share the role of transdisciplines, ranging from government science, institutional economics, political economy, engineering science, ecology, business, to socilogy and other sciences. Keywords: transdisciplinary, port management, marine services